Automobile, construction and entertainment business sector influences on sedentary lifestyles. (25th August 2016) - Parra, Diana C; de Sá, Thiago H; Monteiro, Carlos A; Freudenberg, Nicholas
Abstract: Sedentary lifestyles contribute to premature death and health inequalities. Researchers have studied personal and community-level determinants of inactivity but few have analyzed corporate influences. To reframe the public health debate on inactivity and open new doors for public sector intervention, we conducted a scoping review of evidence from several disciplines to describe how the business and political practices of the automobile, construction, and entertainment sectors have encouraged sedentary lifestyles. In the last 50 years, these industries have found it profitable to produce motor vehicles, housing, and entertainment, which intentionally or unintentionally discourage physical activity. Ceding primary authority for policy decisions in these sectors to the market-based economy has enabled the growth of powerful lobbies that encourage and maintain sedentary lifestyles. To counteract these influences, public health and civil society need to confront more upstream economic and social determinants of sedentary lifestyles. Building on evidence from efforts to change harmful tobacco, alcohol and food industry practices, we propose the creation of research and policy agendas that contribute to public health practice that can modify corporate practices that contribute to physical, social and political environments that discourage physical activity.